2019
DOI: 10.1371/journal.pone.0219610
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-based herbicides at low doses affect canonical pathways in estrogen positive and negative breast cancer cell lines

Abstract: Glyphosate is a broad-spectrum herbicide that is used worldwide. It represents a potential harm to surface water, and when commercially mixed with surfactants, its uptake is greatly magnified. The most well-known glyphosate-based product is Roundup. This herbicide is potentially an endocrine disruptor and many studies have shown the cytotoxicity potential of glyphosate-based herbicides. In breast cancer (BC) cell lines it has been demonstrated that glyphosate can induce cellular proliferation via estrogen rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 24 publications
0
19
0
4
Order By: Relevance
“…Also, in the final model, women 50 years of age and older who reported early menarche were 2.08 times more likely to develop breast cancer. This finding is significant, especially due to two aspects: First, it shows that the increasing trend in cancer incidence cannot be attributed only to the ageing of the population, but also due to the diffusion of carcinogenic agents in the environment [22]; second, it reinforces the hypothesis that chronic exposure to low doses of pesticides in different life cycles of human development produces a general increase in carcinogenic processes [22,34]. In the same vein, a meta-analysis study including 118,964 women with invasive breast cancer and 306,091 without the disease found that the risk for the disease increased by 5% for each year of early onset menarche [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in the final model, women 50 years of age and older who reported early menarche were 2.08 times more likely to develop breast cancer. This finding is significant, especially due to two aspects: First, it shows that the increasing trend in cancer incidence cannot be attributed only to the ageing of the population, but also due to the diffusion of carcinogenic agents in the environment [22]; second, it reinforces the hypothesis that chronic exposure to low doses of pesticides in different life cycles of human development produces a general increase in carcinogenic processes [22,34]. In the same vein, a meta-analysis study including 118,964 women with invasive breast cancer and 306,091 without the disease found that the risk for the disease increased by 5% for each year of early onset menarche [35].…”
Section: Discussionmentioning
confidence: 99%
“…This means that a large part of its population is exposed directly or indirectly to pesticides. The most used active ingredients of pesticides used in soybean, corn, and sugarcane crops are Glyphosate, 2,4 Dichlorophenoxyacetic, and Trifuralin, which have been associated with breast cancer [22,23,24]. In addition, in 2018, breast cancer was the most commonly reported, representing 48.98% of all registered cases of cancer among women in Brazil [25].…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate is an endocrine disruptor in chronic ingestion, exhibiting high cytotoxicity. The previously obtained results [ 36 ] show that it affects survival due to deregulation of the cell cycle and metabolic changes that can alter mitochondrial oxygen consumption, increase free radical levels, damage DNA, cause hypoxia, accumulation of mutations and, ultimately, cell death. It was also shown that after exposure to the herbicide for 8 days at a concentration of 0.95 mg/L, there was an increase in the amount of TBARS in muscle and brain tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Walsh et al [ 186 ] detected disturbed progesterone yield, but only with the full formula, which altered puberty progression and reduced serum testosterone in pre-pubertal Wistar rats at 5 mg kg −1 day −1 . Some authors [ 187 , 188 , 189 ] recognized the non-monotonicity of glyphosate itself on a human hormone-reliant cell line of breast cancer. They found the effect to be propitiated by the oestrogen feedback and hindered by inclusion of an oestrogen receptor antagonist.…”
Section: Glyphosate-based Herbicides and Cancer Risksmentioning
confidence: 99%